The relationship between experience and planning theory. - Reuter, Wolf; Jessen, Johann (Taylor & Francis, 2019)
This paper focuses an experience in planning. What is its role in planning practice? What are the implications for planning theory? Planning theorists have looked at experience as a crucial element in the work of planners from different perspectives, and placed it with differing weights in their models of planning. The commonly held view is that experience plays a distinctive role in die practice of planners. This paper reviews how experience is perceived and examines its nature. It gives an account of its manifestations and locates it as an integral part in a theory of planning. We intend to theorise die relationship between experience and planning. We propose that experience is a decisive variable in the relationship between the practice of planning and the theory of planning.
Keywords: Planungstheorie; Planer; Erfahrung; Kompetenz; Planungspraxis